2020
DOI: 10.1177/0269215520965054
|View full text |Cite
|
Sign up to set email alerts
|

“Short- and mid-term effects of adding upper cervical manual therapy to a conventional physical therapy program in patients with chronic mechanical neck pain. Randomized controlled clinical trial.”

Abstract: Objective: To evaluate the effect of adding an Upper Cervical Translatoric Mobilization (UCTM) or an Inhibitory Suboccipital Technique (IST) to a physiotherapy treatment in the symptomatology and function of mechanical chronic neck pain patients. Design: Randomized controlled trial. Setting: Primary Care Center in Cornellà, Spain. Subjects: 78 patients (64 women), with mean age (SD) of 59.96 (13.30) years with mechanical chronic neck pain were divided in three groups: control, IST and UCTM groups. Intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
6
0
2
Order By: Relevance
“…Lack of mobility and symptoms arising from upper cervical spine are considered to be the main indication for upper cervical manual therapy approach ( Kaltenborn, 2012 ; Hidalgo García et al, 2016 ; Malo-Urriés et al, 2017 ; González-Rueda et al, 2021 ; Rodríguez-Sanz et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lack of mobility and symptoms arising from upper cervical spine are considered to be the main indication for upper cervical manual therapy approach ( Kaltenborn, 2012 ; Hidalgo García et al, 2016 ; Malo-Urriés et al, 2017 ; González-Rueda et al, 2021 ; Rodríguez-Sanz et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…4,46,61,115 The remaining 22 trials (78.6%; n = 22/28) were at "high risk" of bias for all the investigated outcomes (FIGURE 2). 2,10,24,35,36,39,42,[48][49][50][51]64,68,71,75,85,86,88,[95][96][97][98]…”
Section: Risk Of Biasmentioning
confidence: 99%
“…Cervical SMT vs CPG-recommended interventions Seventeen trials (19 comparisons) compared the effects on pain at short term 2,4,24,35,39,41,42,[49][50][51]64,71,86,[95][96][97][98] with a statistically significant effect favoring cervical SMT (SMD, 0.66; 95% CI: 0.97, 0.35; I 2 = 83%; very low evidence certainty) and 9 trials (10 comparisons) at long term 2,24,35,39,42,51,85,86,96 with a statistically significant effect favoring cervical SMT (SMD, 0.73; 95% CI: 1.16, 0.31; I 2 = 85%; very low evidence certainty) (FIGURE 3). Data could not be retrieved from 3 trials.…”
Section: Effects Of Interventions Primary Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies have shown that applying a C0-C1 mobilization treatment versus a control/sham group or adding it to a standardized physiotherapy treatment generates benefits in patients with chronic neck pain and upper cervical rotation restriction in pain and range of motion [9,[14][15][16][17][18]. Also, increasing upper cervical mobility is associated with the improvement of deep muscle recruitment, since there is a linear relationship between the range of motion of the upper cervical spine and the contractile capacity of the deep cervical musculature [19].…”
Section: Introductionmentioning
confidence: 99%